EFFECT OF HORMONE-ACTIVE METABOLITES OF CHOLECALCIFEROL ON THE STATE OF THE ORAL CAVITY TISSUES IN RATS UNDER THE CONDITIONS OF ESTROGEN DEFICIENCY AND TRAUMATIC STRESS - Schnaider, S.A.; Humeniuk, V.V.; Horokhivskyi, V.N.; Yefremova, O.V.; Khristova, M.T.; Tkachenko, Ye.K. (World of Medicine and Biology, 2020)
The purpose of the study was to comparatively establish the effect of active metabolites of vitamin D3 on the periodontal condition of rats under conditions of experimental estrogen deficiency and traumatic stress. The experiment was carried out on 31 female breeding Wistar rats. 1st group was intact one (8 animals). The rats of the 2nd - 4th groups underwent ovariectomy and a femoral fracture. Group 2 was control one (8 rats); rats of the 3rd and 4th groups received per os preparations against the background of the pathogenic effect: Group 3 (8 rats) – 1-α-hydroxycholecalciferol at a dose of 0.1 μg per day per rat; in the Group 4 (7 rats) – 24,25-hydroxycholecalciferol at a dose of 1.25 μg per day/rat. At the time of sacrifice, the animals were 15 months old. Under the influence of risk factors for periodontitis, protective properties of hormone-active metabolites of vitamin D3 were observed. They were expressed in inhibition of lipid peroxidation processes in the oral mucosa of rats, as well as periodontal protective effects when using 24,25-hydroxycholecalciferol.
Keywords: vitamin D3 metabolites; estrogen deficiency; traumatic stress; periodontal protection properties; antioxidant effect; rats